1989
DOI: 10.1002/j.1460-2075.1989.tb03385.x
|View full text |Cite
|
Sign up to set email alerts
|

Wheat dwarf virus, a geminivirus of graminaceous plants needs splicing for replication.

Abstract: By analysing mRNAs with the polymerase chain reaction (PCR) and by studying in vitro generated mutants we have identified an intron in the genome of wheat dwarf virus (WDV), a geminivirus of cereals. Polypeptides whose expression is essential for the replication of the viral DNA have been defined. They are encoded by two distinct overlapping open reading frames (ORFs). The joining of these two ORFs by deletion of the intron as well as the introduction of a frameshift mutation within the intron do not prevent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 23 publications
2
85
0
2
Order By: Relevance
“…The ORF C2, which as with WDV-S, DSV and CSMV lacked an ATG initiation codon, was highly conserved. This high conservation of the C20RFs and the demonstration of the requirement of C2 for the replication of WDV (Schalk et al, 1989) suggest that it is likely to be functional. The C 1 and C20RFs of MiSV do not overlap as extensively as their counterparts in MSV, WDV, CSMV and DSV.…”
Section: Comparisons With Other Monocot-infecting Geminivirusesmentioning
confidence: 84%
See 1 more Smart Citation
“…The ORF C2, which as with WDV-S, DSV and CSMV lacked an ATG initiation codon, was highly conserved. This high conservation of the C20RFs and the demonstration of the requirement of C2 for the replication of WDV (Schalk et al, 1989) suggest that it is likely to be functional. The C 1 and C20RFs of MiSV do not overlap as extensively as their counterparts in MSV, WDV, CSMV and DSV.…”
Section: Comparisons With Other Monocot-infecting Geminivirusesmentioning
confidence: 84%
“…It has been shown that splicing of the complementarysense transcript is necessary for the replication of WDV-S in Tritieum monococcum protoplasts (Schalk et al, 1989), and has also been detected in DSV replication (Accotto & Mullineaux, 1989;Mullineaux et al, 1990). Examination of the C1/C2 sequences of MiSV revealed the presence of putative 5 and 3 splice junctions and likely branch point sequences (Brown, 1986), at positions equivalent to those in the genome of other monocotinfecting viruses (data not shown).…”
Section: Comparisons With Other Monocot-infecting Geminivirusesmentioning
confidence: 93%
“…In fact, similarly to viruses within the genera Mastrevirus and Becurtovirus (Dekker et al, 1991;Morris et al 1992;Mullineaux et al, 1990;Schalk et al, 1989;Varsani et al, 2014b;Wright et al, 1997), and to EcmLV (Bernardo et al, 2013) and GRBaV (Al Rwahnih et al, 2013), the FGENESH program predicted the presence of an intron in the complementary-sense transcript (from positions 2236 to 2136 in the MMDaV genome) (Fig. 4a).…”
Section: Y Ma and Others 2426mentioning
confidence: 93%
“…ORF C2 does not contain an appropriately placed ATG, suggesting that it is expressed by post-transcriptional processing as has been demonstrated for digitaria streak virus (DSV), WDV and TYDV (Accotto et al, 1989 ;Schalk et al, 1989 ;Morris et al, 1992). To investigate splicing in BeYDV, total nucleic acids were extracted from infected D. stramonium plants agroinoculated with cloned viral DNA, and highmolecular-weight RNAs were isolated by salt precipitation and treated with DNase I (Pharmacia) as described by Covey & Hull (1981).…”
Section: Cbbementioning
confidence: 99%